2021
DOI: 10.1021/acsami.1c11316
|View full text |Cite
|
Sign up to set email alerts
|

Antifouling Fibrous Membrane Enables High Efficiency and High-Flux Microfiltration for Water Treatment

Abstract: Membrane biofouling has long been a major obstacle to highly efficient water treatment. The modification of the membrane surface with hydrophilic materials can effectively enhance biofouling resistance. However, the water flux of the membranes is often compromised for the improvement of antifouling properties. In this work, a composite membrane composed of a zwitterionic hydrogel and electrospinning fibers was prepared by a spin-coating and UV cross-linking process. At the optimum conditions, the composite mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Although GO is inactive within the visible range, its presence could increase the apparent quantum efficiency, thus improving the photocatalytic properties. 48 The UV crosslinking mechanism was addressed in section 3.1.7. The antifouling capability of the prepared composite membranes comes from CMBA, a zwitterionic material, which could prevent protein and microbial adhesion.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…Although GO is inactive within the visible range, its presence could increase the apparent quantum efficiency, thus improving the photocatalytic properties. 48 The UV crosslinking mechanism was addressed in section 3.1.7. The antifouling capability of the prepared composite membranes comes from CMBA, a zwitterionic material, which could prevent protein and microbial adhesion.…”
Section: Wastewater Treatmentmentioning
confidence: 99%
“…10,11 To remove dyes and Pb 2+ from wastewater, various methods, including ion exchange, physical adsorption, activated carbon removal, chemical precipitation, and biodegradation, have been reported for industrial wastewater treatment. [12][13][14][15] Among these techniques, adsorption is preferred owing to its facile implementation, low energy consumption, economic feasibility, and high efficiency. 16 Li et al developed a hydrogel using epichlorohydrin and ethylenediamine to remove toxic dyes.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 k-Casein is a hydrophobic compound presented on the surface of casein micelles, which enables casein to form a micellar structure in a hydrated state. 4,32 The product of the redox initiator, SO 4 2− , as a strongly hydrated ion, can reduce the solubility of casein due to the Hofmeister effect: the interaction of macromolecules and ions removes the water of hydration from the protein and folds the protein, prompting casein to form a three-dimensionally (3D) cured structure through hydrophobic association. 33 In particular, casein micelles are composed of many sub-micelles that can be rearranged by applying shear force.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Hydrogels are promising candidate materials for wearable exible electronic devices due to their tissue-like high water-containing chemical structure, exibility, and conductivity. [4][5][6][7][8] Among them, tough hydrogels are widely used in various elds due to their excellent mechanical properties. Numerous studies have shown that free radical polymerization of vinyl monomers is a simple and versatile method for building tough covalent hydrogel networks.…”
Section: Introductionmentioning
confidence: 99%